Lithium metal batteries and their applications
By using gel electrolyte with a semi-interpenetrating network structure in lithium metal batteries, the problem of insufficient mechanical properties of gel electrolytes in the prior art is solved, and the higher circulation performance and safety performance of lithium metal batteries are achieved.
Patent Information
- Application Number
- CN202210920466.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-02
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-08-02
AI Technical Summary
In order to achieve excellent contact effect with the electrode sheet, the gel electrolyte in the existing lithium metal battery sacrifices some of the mechanical properties, making it difficult to maintain structural stability during the cycle.
A gel electrolyte with a semi-interpenetrating network structure including uncrosslinked polymers and three-dimensional organic crosslinking networks is adopted to improve the mechanical properties and interface contact ability of the gel electrolyte through the semi-interpenetrating network structure formed by interspersing between the uncrosslinked polymers and the three-dimensional organic crosslinking network.
The gel electrolyte is achieved with excellent contact with the electrode sheet while ensuring its structural integrity during the battery circulation process, thereby improving the circulation and safety performance of lithium metal batteries.
Smart Images

Figure CN115275336B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium metal battery and its application. Background Art
[0002] In recent years, the demand for high energy density lithium-ion batteries has been increasing. At present, commercial lithium battery graphite negative electrodes are difficult to meet the demand for high energy density lithium-ion batteries. Lithium metal has a low standard electrode potential (-3.045V) and a large theoretical gram capacity (3860mAh / g). When matched with high energy density positive electrode materials, it can achieve a higher operating voltage and energy density; however, due to its extremely active metallic properties, lithium metal is prone to side reactions with the electrolyte, thereby consuming the lithium metal itself and the electrolyte, resulting in a lower coulombic efficiency.
[0003] During the charging process of lithium metal batteries, the current density and the uneven distribution of lithium ions in the electrolyte can easily cause lithium ions to deposit locally on the lithium metal surface, thereby forming a dendrite structure, which reduces the deposition density of lithium ions. In severe cases, lithium dendrites can pierce the diaphragm, causing serious safety problems. During the charge-discharge process, the lithium metal negative electrode will experience severe volume expansion and contraction. The drastic volume change can easily cause the surface protective layer to break and peel off, and lose its protective effect.
[0004] Solid-state electrolytes can effectively inhibit side reactions at the lithium metal interface and the safety issues caused by lithium dendrites, but most solid-state electrolytes are difficult to form excellent interface contact with the electrode. The low ionic conductivity of polymer solid electrolytes and the poor processing and mechanical properties of inorganic solid electrolytes seriously limit their application in actual products. Gel electrolytes have the advantages of both liquid electrolytes and solid electrolytes, but gel electrolytes will sacrifice some mechanical properties to achieve excellent contact with the electrode, and mechanical properties are the key factor in maintaining the structural stability of gel electrolytes during the charge / discharge cycle. Summary of the invention
[0005] The embodiments of the present application provide a lithium metal battery and its application, which can solve the problem in the prior art that the gel electrolyte sacrifices some mechanical properties in order to achieve excellent contact with the electrode, making it difficult to maintain structural stability during the cycle process.
[0006] In the first aspect, the embodiment of the present application provides a lithium metal battery, including: a gel electrolyte; the gel electrolyte includes an uncrosslinked polymer and a three-dimensional organic crosslinked network, and the uncrosslinked polymer and the three-dimensional organic crosslinked network are interlaced to form a semi-interpenetrating network structure. Wherein, the three-dimensional organic crosslinked network is a gel-state elastic network, which has the characteristic that the storage modulus is greater than the loss modulus, and the gel-state elastic network is used to improve the mechanical properties of the gel electrolyte; the uncrosslinked polymer is not bound by chemical crosslinking points, and has a high degree of freedom of the interface polymer chain, which is used to improve the interface contact ability of the gel electrolyte; the uncrosslinked polymer forms a physical crosslinking point with the three-dimensional organic crosslinked network by non-covalent crosslinking, thereby forming the semi-interpenetrating network structure, which is used to simultaneously improve the mechanical properties of the gel electrolyte and the freedom of movement of the surface polymer chain, so as to achieve excellent contact between the gel electrolyte and the pole piece, and at the same time, it can also ensure its structural integrity during the battery cycle, thereby improving the cycle performance and safety performance of the lithium metal battery; the rheological performance test of the gel electrolyte has an obvious loss angle.
[0007] In some embodiments, the three-dimensional organic cross-linked network includes a monomer containing a polymerizable group; wherein the polymerizable group includes any one of a double bond, an amino group, a carboxyl group or a hydroxyl group, and the monomer includes at least one of methacrylate, sodium acrylate, acrylamide, vinylene carbonate, adipic acid, and polyethylene glycol.
[0008] In some embodiments, the molar amount of the monomer containing a polymerizable group is n′, and the molar amount of the cross-linking agent is n″, satisfying: 10:1≤n′ / n″≤1000:1.
[0009] In some embodiments, the uncrosslinked polymer satisfies at least one of the following conditions: Condition a: the degree of polymerization DP of the uncrosslinked polymer satisfies: 1000≤DP≤100000; Condition b: the length of the Kuhn segment in the uncrosslinked polymer is less than 5 nm.
[0010] In some embodiments, the uncrosslinked polymer includes at least one of polyoxyethylene, terminal-modified polyoxyethylene, polyurethane, polycarbonate, or polyphosphate;
[0011] In some embodiments, the uncrosslinked polymer includes terminal amino-modified polyethylene oxide.
[0012] In some embodiments, based on the mass of the gel electrolyte, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 10 to 0.5:1.
[0013] In some embodiments, based on the mass of the gel electrolyte, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 1 wt % to 10 wt %.
[0014] In some embodiments, the gel electrolyte has a loss angle tanδ>1.
[0015] In some embodiments, at least one of the following conditions is met:
[0016] (1) The degree of polymerization DP of the uncrosslinked polymer satisfies: 5000≤DP≤7000;
[0017] (2) The three-dimensional organic cross-linked network is obtained by polymerization of a monomer and a cross-linking agent, the molar weight of the monomer is n′, the molar weight of the cross-linking agent is n″, and the following conditions are satisfied: 50:1≤n′ / n″≤200:1;
[0018] (3) Based on the mass of the gel electrolyte, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 3% to 5%;
[0019] (4) Based on the mass of the gel electrolyte, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 2:1 to 0.8:1.
[0020] In a second aspect, the present invention provides a method for preparing a lithium metal battery, comprising the following steps:
[0021] (1) Preparation of a gel electrolyte precursor solution: adding a crosslinking agent to an electrolyte solution containing a monomer having a polymerizable group and an uncrosslinked polymer to obtain a precursor solution;
[0022] (2) Inject the precursor solution obtained in step (1) into the battery cell and react at 65°C to 75°C.
[0023] In a third aspect, an embodiment of the present application provides an electrical device, wherein the electrical device comprises any one of the above-mentioned lithium metal batteries.
[0024] The beneficial effects brought about by the technical solutions provided by some embodiments of the present application include at least:
[0025] The semi-interpenetrating network structure of the gel electrolyte in the embodiment of the present application not only has good bonding strength with the electrode, which is beneficial to suppress the uneven contact between the electrode and the gel electrolyte caused by the volume expansion of the electrode during the charge and discharge process, but also has good mechanical properties, which is beneficial to maintain the structural stability during the cycle process, thereby improving the cycle performance and safety performance of the lithium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 Schematic diagram of the structure of the gel electrolyte in the embodiment of the present application (the black lines are three-dimensional organic cross-linked networks, and the gray lines are uncross-linked polymers). DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0030] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.
[0031] Polymer solid electrolytes have good flexibility and safety. They can be obtained by dissolving lithium salts in polymers and then drying the coating. Lithium ions can move through the movement of chains. The number of free lithium ions and the mobility of chains significantly affect the transmission efficiency of lithium ions. However, polymer electrolytes usually have low room temperature ionic conductivity (10 -6 ~10 -5S / cm), poor compatibility with metallic lithium anodes, and structural instability during cycling; inorganic solid electrolytes, whose room temperature ionic conductivity can be as high as 10 -4 ~10 -2 S / cm, but after replacing the organic electrolyte with an inorganic solid electrolyte, the solid-liquid interface of the electrode material / electrolyte in the lithium battery system is also replaced by the solid-solid interface of the electrode material / solid electrolyte. The interfacial contact between the solid-solid interfaces of the inorganic solid electrolyte is extremely poor, resulting in a very high interfacial impedance. Although the inorganic solid electrolyte has high mechanical strength, its flexibility is poor.
[0032] The network structure inside the gel electrolyte has a great influence on its performance. For example, a gel network with a high degree of crosslinking has excellent mechanical properties, which is conducive to maintaining its structural stability during the battery cycle and has a certain inhibitory effect on the formation of lithium dendrites. However, for a gel network with a high degree of crosslinking, the polymer chains at its interface are restrained by its internal high-density crosslinking structure and do not have excellent mobility. Therefore, a gel network with a high degree of crosslinking cannot form sufficient contact with the electrode, which easily causes uneven current to form on the surface of the electrode during the battery cycle, and then produces uneven lithium deposition problems, which ultimately affects the battery's cycle life and safety performance; while a gel network with a low degree of crosslinking has excellent interface contact ability, but does not have excellent mechanical properties, and it is difficult to maintain its structural stability during the cycle.
[0033] Therefore, there is no gel electrolyte in the prior art that has both excellent mechanical properties and good interface contact.
[0034] Lithium Metal Batteries
[0035] In order to solve the above technical problems, the present application proposes a lithium metal battery, including a positive electrode plate, a separator, a negative electrode plate and a gel electrolyte.
[0036] Gel Electrolyte
[0037] The gel electrolyte comprises uncrosslinked polymers and a three-dimensional organic crosslinked network, wherein the uncrosslinked polymers and the three-dimensional organic crosslinked network interpenetrate each other to form a semi-interpenetrating network structure; and an obvious loss angle is observed in a rheological property test of the gel electrolyte.
[0038] The three-dimensional organic cross-linked network is a gel-state elastic network, which has the characteristics of a storage modulus greater than a loss modulus. The high cross-linking density and high elastic modulus of the three-dimensional organic cross-linked network give it excellent mechanical properties, which is conducive to maintaining its structural stability during the battery cycle and also has a certain inhibitory effect on the formation of lithium dendrites.
[0039] The uncrosslinked polymer is not bound by chemical crosslinking points and has a high degree of freedom of the interface polymer chain, so as to achieve excellent interface contact ability with the electrode;
[0040] The uncrosslinked polymer forms temporary physical crosslinking points with the three-dimensional organic crosslinking network by non-covalent crosslinking, so as to simultaneously improve the mechanical properties of the gel electrolyte and the freedom of movement of the surface polymer chains, which can break the negative coupling relationship between the body mechanics of the gel electrolyte and the freedom of the surface polymer chains in the prior art, and achieve a double improvement of the two, ensuring that the gel electrolyte has excellent contact with the pole piece while also ensuring its structural integrity during the battery cycle, thereby improving the cycle performance and safety performance of the lithium metal battery; moreover, the gel electrolyte is obtained by in-situ polymerization under high temperature conditions using an electrolyte solution containing both a polymerizable group and an uncrosslinked polymer as a precursor solution.
[0041] In some embodiments, the three-dimensional organic cross-linked network includes monomers containing polymerizable groups; the polymerizable groups include any one of double bonds, amino groups, carboxyl groups, or hydroxyl groups; the polymerization includes, but is not limited to, any one of free radical polymerization and condensation polymerization. The double bonds are mainly suitable for free radical polymerization, and the amino groups, carboxyl groups, and hydroxyl groups are mainly suitable for condensation polymerization.
[0042] In some embodiments, the monomer includes at least one of methacrylate, sodium acrylate, acrylamide, vinylene carbonate, adipic acid, and polyethylene glycol.
[0043] In some embodiments, the molar amount of the monomer containing a polymerizable group is n', and the molar amount of the cross-linking agent is n", satisfying: 10:1≤n' / n"≤1000:1; the cross-linking density of the three-dimensional organic cross-linked network is determined by the molar ratio of the monomer and the cross-linking agent, and the greater the cross-linking density of the three-dimensional organic cross-linked network, the better its mechanical properties are, and it is more conducive to maintaining the structural stability of the gel electrolyte. In some embodiments, n' / n" is 100:1.
[0044] Illustratively, the ratio of the molar amount n′ of the monomer containing the polymerizable group to the molar amount n″ of the cross-linking agent is 10:1, 80:1, 120:1, 200:1, 400:1, 600:1, 800:1, 1000:1 or a range consisting of any two of the above values.
[0045] In some embodiments, the crosslinking agent is a compound containing multiple unsaturated double bonds in the molecule, including but not limited to one or more of divinylbenzene, diisocyanate, N,N-methylenebisacrylamide, and polyethylene oxide (PEO) modified with terminal double bonds.
[0046] In some embodiments, the uncrosslinked polymer satisfies at least one of the following conditions: Condition a: the degree of polymerization DP of the uncrosslinked polymer satisfies: 1000≤DP≤100000; Condition b: the length of the Kuhn segment in the uncrosslinked polymer is less than 5 nm. In some embodiments, the degree of polymerization DP of the uncrosslinked polymer is 6000.
[0047] For condition a, if the molecular weight of the uncrosslinked polymer is too low (for example, DP < 1000), it is impossible to form an entanglement interaction force with the three-dimensional organic crosslinked network, which is not conducive to the improvement of the mechanical properties of the gel electrolyte. The entanglement between the uncrosslinked polymer and the three-dimensional organic crosslinked network can improve the mechanical properties of the gel electrolyte; if the molecular weight of the uncrosslinked polymer is too high (for example, DP > 100000), the entanglement between it and the three-dimensional organic crosslinked network is more obvious, resulting in its movement at the electrode interface being restricted, which is not conducive to the improvement of the gel electrolyte interface adhesion. For condition b, the Kuhn segment is used to characterize the flexibility of the polymer chain. In order to make the movement of the uncrosslinked polymer at the electrode interface unrestricted and have a high degree of freedom of movement, the length of the Kuhn segment in the uncrosslinked polymer must be less than 5nm.
[0048] Illustratively, the degree of polymerization DP of the uncrosslinked polymer is 1000, 3000, 5000, 7000, 10000, 50000, 100000 or a range consisting of any two of the above values.
[0049] Exemplarily, the length of the Kuhn segment in the uncrosslinked polymer is 0.01 nm, 2 nm, 4 nm, or a range consisting of any two of the above values.
[0050] In some embodiments, the uncrosslinked polymer includes at least one of polyoxyethylene, terminal-modified polyoxyethylene, polyurethane, polycarbonate or polyphosphate; preferably, the terminal-modified polyoxyethylene includes terminal amino-modified polyoxyethylene (N-PEO).
[0051] In some embodiments, based on the mass of the gel electrolyte, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 10-0.5: 1. In some embodiments, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 1:1.
[0052] The addition of uncrosslinked polymers can improve both the mechanical properties and interfacial adhesion of gel electrolytes, but different proportions of addition have different degrees of improvement on the two properties. The physical entanglement of the three-dimensional organic crosslinked network comes from the uncrosslinked polymers. In the case of the same content of the three-dimensional organic crosslinked network, the more the content of the uncrosslinked polymers, the more physical interactions between the two, and the greater the degree of inhibition on the surface movement of the gel electrolyte; it can be seen that too high a mass content of uncrosslinked polymers (for example, a mass ratio greater than 10:1) has little effect on the improvement of mechanical properties. The improvement of the mechanical properties of the gel electrolyte mainly comes from the three-dimensional organic crosslinked network and its high crosslinking density. Too high a proportion of uncrosslinked polymers will affect the content of the three-dimensional organic crosslinked network; while too low a mass content of uncrosslinked polymers (for example, a mass ratio less than 0.5:1) is not conducive to the improvement of interfacial adhesion.
[0053] Illustratively, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 10:1, 8:1, 6:1, 4:1, 2:1, 1.5:1, 0.8:1, 0.5:1 or a range consisting of any two of the above values.
[0054] In some embodiments, based on the mass of the gel electrolyte, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 1wt% to 10wt%. In some embodiments, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 4wt%.
[0055] The mass content of the uncross-linked polymer and the mass content of the three-dimensional organic cross-linked network are collectively referred to as the solid content; if the solid content is too low (for example, the solid content is lower than 1wt%), the mechanical properties of the gel electrolyte are too weak; if the solid content is too high (for example, the solid content is higher than 10wt%), it has poor adhesion to the electrode interface and is prone to form gaps with the electrode.
[0056] Illustratively, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt% or a range consisting of any two of the above values.
[0057] In some embodiments, the gel electrolyte has a loss angle tanδ>1.
[0058] The uncross-linked polymer does not react with the three-dimensional organic cross-linked network, but there are strong physical interactions, such as hydrogen bond interactions, electrostatic interactions or entanglement between polymer chains. In rheological tests, the three-dimensional organic cross-linked network interspersed and entangled with the uncross-linked polymer can be destroyed and rebuilt during the dynamic shear process, thereby absorbing energy and having an obvious loss angle (tan>1).
[0059] In some embodiments, the degree of polymerization DP of the uncrosslinked polymer satisfies: 5000≤DP≤7000.
[0060] Illustratively, the degree of polymerization DP of the uncrosslinked polymer is 5000, 5500, 6000, 6500, 7000 or a range consisting of any two of the above values.
[0061] In some embodiments, the three-dimensional organic cross-linked network is obtained by polymerization of a monomer and a cross-linking agent, the molar weight of the monomer is n′, the molar weight of the cross-linking agent is n″, and the following relationship is satisfied: 50:1≤n′ / n″≤200:1.
[0062] Illustratively, the ratio of the molar amount n′ of the monomer containing the polymerizable group to the molar amount n″ of the cross-linking agent is 50:1, 100:1, 150:1, 200:1 or a range consisting of any two of the above values.
[0063] In some embodiments, based on the mass of the gel electrolyte, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 3% to 5%.
[0064] Illustratively, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of the above values.
[0065] In some embodiments, based on the mass of the gel electrolyte, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 2:1 to 0.8:1.
[0066] Illustratively, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 2:1, 1:1, 0.8:1 or a range consisting of any two of the above values.
[0067] other
[0068] The electrolyte is a common commercial lithium-ion electrolyte, including an organic solvent and a lithium salt;
[0069] The organic solvent includes carbonate solvents, ether solvents, sulfone solvents, other aprotic solvents or combinations thereof;
[0070] Wherein, the carbonate solvent includes one or more combinations of diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate.
[0071] The ether solvent includes one or more combinations of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl1,3-dioxolane, 4-methyl1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, dimethoxypropane, dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane or 1,2-ethoxymethoxyethane.
[0072] The sulfone solvents include sulfolane, dimethyl sulfoxide, methyl sulfolane, etc. Other organic solvents include 1,3-dimethyl-2-imidazolidinone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester.
[0073] Lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis(oxalatoborate) (LiB(C2O4)2, LiBOB), lithium difluorooxalatoborate (LiBF2(C2O4, LiDFOB), lithium tetrafluoroborate (LiBF4), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium perfluorobutylsulfonate (LiC4F9SO3), lithium perchlorate (LiClO4), lithium aluminate (LiAlO2), lithium tetrachloroaluminate (LiAlCl4), lithium bis(sulfonyl imide) (LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2), wherein x and y are natural numbers), a combination of one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium chloride (LiCl) or lithium fluoride (LiF).
[0074] The electrolyte may further include an electrolyte additive, and the electrolyte additive may be, but is not limited to, one or more of fluoroethylene carbonate (FEC) and fluorodimethyl carbonate (FDMC).
[0075] Preparation of gel electrolyte
[0076] The main steps include:
[0077] (1) Preparation of a gel electrolyte precursor solution: preparing an electrolyte solution, adding a crosslinking agent to an electrolyte solution containing a monomer having a polymerizable group and an uncrosslinked polymer to obtain a precursor solution;
[0078] The mass ratio of electrolyte: polymerizable monomer: uncross-linked long-chain polymer is 90-99: 0.67-6.67: 0.37-9.1.
[0079] (2) Injecting the precursor solution obtained in step (1) into the battery cell and reacting at 65° C. to 75° C.; preferably, injecting the precursor solution into the battery cell and reacting at a temperature of 70° C. for 12 hours.
[0080] During the preparation of the gel electrolyte, the uncrosslinked polymer is pre-mixed into an electrolyte containing a polymerizable monomer (a monomer containing a polymerizable group), and under the action of an initiator, in-situ polymerization is performed to form a composite structure having a three-dimensional organic crosslinked network (elastic network) and uncrosslinked polymers interpenetrating in space; and the gel electrolyte has a tensile elastic modulus greater than 50 kPa, and a plate adhesion strength of more than 50 kPa when the fracture strain is greater than 100%. The in-situ polymerization method includes but is not limited to one of thermal initiation, ultraviolet initiation or radiation initiation.
[0081] In some embodiments, the initiator includes one or more of benzoyl peroxide, potassium persulfate, ammonium persulfate, azobisisobutyronitrile or azobisisoheptanenitrile.
[0082] The mechanical properties of gel electrolyte are mainly affected by the three-dimensional organic cross-linked network. If it contains a high cross-linking density, the mechanical properties are excellent, which is conducive to maintaining the structural integrity of the gel electrolyte body and better inhibiting the formation of lithium dendrites; but too high a cross-linking density will have a greater inhibitory effect on the freedom of movement of the polymer chains on the surface of the gel electrolyte (i.e., uncross-linked polymers). The freedom of movement of the surface polymer chains will be inhibited due to the restraint of the internal cross-linking structure. When in contact with the electrode, the polymers on the surface of the gel electrolyte (i.e., uncross-linked polymers) cannot fully infiltrate the electrode, forming uneven contact, which easily causes uneven current to form on the surface of the electrode during the battery cycle, and then produces uneven lithium deposition problems, ultimately affecting the cycle and safety performance of the lithium metal battery.
[0083] By introducing uncrosslinked long-chain polymers into the three-dimensional organic cross-linked network in the gel state, the negative coupling relationship between the mechanics of the gel electrolyte bulk and the degree of freedom of the surface polymer chain in the prior art can be broken, thereby achieving a dual improvement of the two. At the same time, through the preparation method of in-situ introduction, the uncrosslinked polymers are confined in the elastic network in the gel state (i.e., the three-dimensional organic cross-linked network) to form a semi-interpenetrating network gel electrolyte. There is a physical interaction between the uncrosslinked polymer and the elastic network, including the physical entanglement of the long-chain polymer (i.e., the uncrosslinked polymer) itself, the hydrogen bonding effect between the long-chain polymer and the elastic network, and the electrostatic effect. The physical interaction formed by the two is equivalent to forming a temporary physical cross-linking point inside the elastic network, which can effectively improve the bulk mechanical properties of the semi-interpenetrating gel electrolyte.
[0084] Moreover, the long-chain polymer shuttles through the elastic network, and its freedom of movement on the surface is only affected by the physical interaction between it and the elastic network and the cross-linking density of the elastic network. Compared with the restraint of chemical bonding, the physical interaction between the uncross-linked polymer and the elastic network can undergo dynamic changes in space, which does not affect the freedom of movement of the uncross-linked polymer chain on the surface of the gel electrolyte.
[0085] In addition, the cross-linking density of the elastic network can be regulated by changing the ratio of the cross-linking agent to the monomer. The gel electrolyte with a semi-interpenetrating network structure with internal interactions can have excellent bulk mechanical properties and interfacial contact capabilities with uniform contact with the electrode surface, thereby improving the cycle and safety capabilities of lithium metal batteries.
[0086] The lithium metal battery can be prepared according to conventional methods in the art.
[0087] Exemplarily, the positive electrode sheet, separator and negative electrode sheet are stacked in order, with the separator being placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain an electrode assembly, or the electrode assembly can be obtained by winding; the electrode assembly is placed in a packaging shell, injected with liquid, packaged, and heated to obtain a lithium metal battery.
[0088] Electrical equipment
[0089] The electrical equipment of the present application includes any one of the above-mentioned lithium metal batteries of the present application. The electrical equipment of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0090] Example
[0091] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0092] Example 1
[0093] Preparation of negative electrode
[0094] The 30 μm thick lithium copper composite tape was cut into specifications of (40 mm×60 mm) for later use.
[0095] Preparation of positive electrode
[0096] The positive electrode ternary active material Ni 0.8 Mn 0.1 Co 0.1 , conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75%, and stirred evenly. The slurry is evenly coated on the positive electrode current collector aluminum foil and dried at 90°C to obtain a positive electrode sheet. After coating, the positive electrode sheet is cut into (38mm×58mm) specifications for standby use.
[0097] Preparation of gel electrolyte
[0098] In a dry argon atmosphere, organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed at a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC) (i.e., monomer), terminal double bond-modified polyethylene oxide (PEO) (i.e., cross-linking agent), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000) (i.e., uncross-linked polymer), azobisisobutyronitrile (i.e., initiator), fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0 M LiPF6 in 1 M. 20% FEC+30% FDMC+20% EC+26% TTE+3.63% (VC+PEO)+0.37% (N-PEO), wherein the molar ratio of VC to PEO is 100:1.
[0099] In the following embodiments, the same substances have the same functions and are not described in detail.
[0100] Preparation of lithium metal batteries
[0101] A polyethylene (PE) with a thickness of 15 μm is selected as the separator, and a Z-shaped stacking method is adopted. The positive electrode and the negative electrode are on both sides of the separator, and the separator is between the electrodes. After stacking, the pole ears are welded. Then they are placed in an aluminum-plastic film, and after top and side sealing, liquid injection, packaging, heating and curing, a lithium metal stacked battery is finally obtained.
[0102] Example 2
[0103] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0104] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (N-PEO), wherein the molar ratio of VC to PEO was 100:1.
[0105] Example 3
[0106] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0107] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+1.33% (VC+PEO)+2.67% (N-PEO), wherein the molar ratio of VC to PEO was 100:1.
[0108] Example 4
[0109] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0110] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+29% TTE+0.5% (VC+PEO)+0.5% (N-PEO), wherein the molar ratio of VC to PEO was 100:1.
[0111] Example 5
[0112] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0113] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+20% TTE+5% (VC+PEO)+5% (N-PEO), wherein the molar ratio of VC to PEO was 100:1.
[0114] Example 6
[0115] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0116] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (N-PEO), wherein the molar ratio of VC to PEO was 100:2.
[0117] Example 7
[0118] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0119] In a dry argon atmosphere, the organic solvent ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (N-PEO), wherein the molar ratio of VC to PEO is 100:4.
[0120] Example 8
[0121] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0122] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), polyoxyethylene (PEO) modified with a double bond at the end, polyurethane (PU, degree of polymerization 7000) (i.e., uncrosslinked polymer), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (PU), wherein the molar ratio of VC to PEO is 100:1.
[0123] Example 9
[0124] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0125] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (N-PEO), wherein the molar ratio of VC to PEO was 10:1.
[0126] Example 10
[0127] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0128] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (N-PEO), wherein the molar ratio of VC to PEO was 1000:1.
[0129] Embodiment 11
[0130] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0131] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 1000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (N-PEO), wherein the molar ratio of VC to PEO was 100:1.
[0132] Example 12
[0133] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0134] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 100000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+2% (VC+PEO)+2% (N-PEO), wherein the molar ratio of VC to PEO was 100:1.
[0135] Example 13
[0136] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0137] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) are first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), terminal double bond-modified polyethylene oxide (PEO), polyurethane (PU, degree of polymerization 7000), terminal amino-modified polyethylene oxide (N-PEO, degree of polymerization 6000), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) are added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte 1M LiPF6in20%FEC+30%FDMC+20%EC+26%TTE+2%(VC+PEO)+1%(PU)+1%(N-PEO) with a lithium salt concentration of 1.0M, wherein the molar ratio of VC to PEO is 100:1.
[0138] Comparative Example 1
[0139] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0140] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), polyoxyethylene modified with a double bond at the end (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M, 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+4% (VC+PEO), wherein the molar ratio of VC to PEO was 100:1.
[0141] Comparative Example 2
[0142] Different from Example 1, the preparation of the gel electrolyte is as follows:
[0143] In a dry argon atmosphere, the organic solvents ethylene carbonate (EC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)propane (TTE) were first mixed in a mass ratio of EC:TTE=2:3, and then vinylene carbonate (VC), polyoxyethylene modified with a double bond at the end (PEO), azobisisobutyronitrile, fluoroethylene carbonate (FEC), fluorodimethyl carbonate (FDMC) and lithium salt lithium hexafluorophosphate (LiPF6) were added to the mixed solution and dissolved and mixed evenly to obtain a gel electrolyte with a lithium salt concentration of 1.0M, 1M LiPF6 in 20% FEC+30% FDMC+20% EC+26% TTE+4% (VC+PEO), wherein the molar ratio of VC to PEO was 100:6.
[0144] Test Method
[0145] (1) Adhesion strength test
[0146] Take 2*2cm 2 The electrode is attached to the surface of the aluminum flat test mold, and a 2*2cm 2 The gel electrolyte sheet is attached to the surface of the electrode (the thickness of the gel electrolyte sheet is 2 mm). The gel electrolyte and the electrode are fully bonded, and the bonding area S = 2*2 cm 2 The test mold was stretched at a uniform speed of 1 mm / min using a universal mechanical testing machine to measure the maximum force F during the separation process of the gel electrolyte and the electrode. The adhesion strength between the gel electrolyte and the electrode = F / S.
[0147] (2) Mechanical testing
[0148] Take a gel electrolyte sheet with a length a of 5 cm, a width b of 2 cm, and a thickness c of 3 mm, and fix it on a universal mechanical testing machine with a clamp in the width direction. The center of the gel electrolyte sheet coincides with the center of the upper and lower clamps, and the distance between the upper and lower clamps is 3 cm. Use the universal mechanical testing machine to stretch the gel electrolyte sheet at a speed of 1.5 cm / min to obtain the real-time tensile force F (N) and displacement L (cm) during the stretching process. Draw a stress-strain curve, where stress = F / (b*c), strain = L*100% / 3, and the fracture strain is the strain when the gel electrolyte breaks. Take the Hu Ke elastic zone of the gel electrolyte before 10% strain to calculate the elastic modulus. The elastic modulus is the ratio of the stress change to the strain change in the Hu Ke elastic zone. (Modulus and strain belong to the same mechanical test, and the two parameters are combined into one test process here)
[0149] (3) Cyclic performance test:
[0150] The comparative examples and embodiments intend to use the cycle performance of the battery cell to characterize the effectiveness of the solution. The specific test method is:
[0151] At 25°C, charge the soft-pack battery to 4.3V at a constant current of 0.3C, and then charge it at a constant voltage to a current of 0.025C. At this time, the soft-pack battery is fully charged. Record the charging capacity at this time, which is the charging capacity of the first cycle. After the soft-pack battery is left to stand for 5 minutes, discharge it to 2.8V at a constant current of 0.5C and leave it to stand for 5 minutes. This is a cyclic charge and discharge process. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Repeat the above charge and discharge cycle until the discharge capacity of the current cycle decays to 80% of the discharge capacity of the first cycle or the battery fails. Among them, the capacity retention rate = the discharge capacity of the current cycle / the discharge capacity of the first cycle.
[0152] The freedom of movement of the polymer chains at the interface of the semi-interpenetrating gel electrolyte is directly related to the wetting of the electrode and the adhesion force. Since the freedom of movement of the polymer chains at the interface is difficult to test directly, the adhesion strength between the semi-interpenetrating gel electrolyte and the electrode is used to indirectly characterize the freedom of the polymer chains on its surface.
[0153] The data of the comparative example and the embodiment are intended to characterize the effectiveness of the scheme by the adhesion strength of the gel electrolyte on the copper foil surface, its own mechanical properties and the cycle performance of the battery. The mechanical test stretching speed is 5cm / min, the battery test cut-off voltage is 2.8~4.3V, and the cycle rate is 03 / 05C. The specific data are shown in Table 1 below.
[0154] Table 1
[0155]
[0156]
[0157] Combined with Table 1 and Figure 1 An analysis is conducted, and the comparison of Examples 1 to 3 shows that the ratio of the three-dimensional organic cross-linked network (elastic network) to the uncross-linked polymer (uncross-linked polymer chain) inside the gel electrolyte of the semi-interpenetrating network structure significantly affects the interfacial adhesion between the gel electrolyte and the electrode, thereby affecting the cycle performance of the lithium metal battery; for example, an excessively high elastic network ratio (such as Example 1) will affect the degree of freedom of the interfacial polymer chain, thereby affecting the adhesion between the gel electrolyte and the electrode, and affecting the cycle performance of the lithium metal battery; while an excessively low elastic network ratio (such as Example 3) cannot ensure the structural integrity of the gel electrolyte during the cycle, thereby affecting the cycle performance of the lithium metal battery; it can be seen that the three-dimensional organic cross-linked network and the uncross-linked polymer are within a suitable mass ratio range, which is beneficial to improving the cycle performance of the lithium metal battery.
[0158] The comparison of Examples 2, 4, and 5 shows that the range of solid content in the gel electrolyte with a semi-interpenetrating network structure will significantly affect the cycle performance of the lithium metal battery; for example, too low a solid content (such as Example 4) cannot provide sufficient interface adhesion and has a low elastic modulus, thereby affecting the cycle performance of the lithium metal battery; and too high a solid content (such as Example 5) causes the polymer chains at the interface of the gel electrolyte to be easily restrained by a denser elastic network and reduce the degree of freedom, resulting in low interface adhesion and low tensile strength, thereby affecting the cycle performance of the lithium metal battery; it can be seen that a suitable solid content is beneficial to improving the cycle performance of the lithium metal battery.
[0159] The comparison of Examples 2, 6, 7, 9, and 10 shows that the crosslinking density of the elastic network in the gel electrolyte of the semi-interpenetrating network structure significantly affects the cycle performance of the lithium metal battery; for example, too high a crosslinking agent dosage (such as Example 9) will limit the freedom of the uncrosslinked polymer shuttling inside the elastic network at the interface, resulting in low bonding strength with the electrode, thereby affecting the cycle performance of the lithium metal battery; while too low a crosslinking agent dosage (such as Example 10) cannot provide sufficient mechanical strength, and thus cannot ensure the structural integrity of the gel electrolyte during the cycle, and will also affect the cycle performance of the lithium metal battery; it can be seen that the elastic network has a suitable crosslinking density, which is beneficial to improving the cycle performance of the lithium metal battery.
[0160] From the comparison of Examples 2, 11, and 12, it can be seen that the degree of polymerization of the uncross-linked polymer in the gel electrolyte of the semi-interpenetrating network structure has a certain influence on the cycle performance of the lithium metal battery; for example, too low a degree of polymerization (such as Example 11) lacks sufficient self-entanglement mechanism, which is not conducive to the improvement of the mechanical properties of the gel electrolyte, and thus affects the cycle performance of the lithium metal battery; while too high a degree of polymerization (such as Example 12) has too many self-entanglement mechanisms, which affects the degree of freedom of the interface polymer, is not conducive to the improvement of the adhesion strength with the electrode, and also affects the cycle performance of the lithium metal battery; it can be seen that the degree of polymerization of the uncross-linked polymer is beneficial to improving the cycle performance of the lithium metal battery within an appropriate range.
[0161] From the comparison of Examples 2, 8, and 13, it can be seen that the uncrosslinked polymer in the gel electrolyte of the semi-interpenetrating network structure can be selected from non-ether polymers, or one or more of the uncrosslinked polymers can be used. For example, the uncrosslinked polymer in Example 2 is polyoxyethylene (N-PEO) modified with terminal amino groups, the uncrosslinked polymer in Example 8 is polyurethane, and the uncrosslinked polymer in Example 13 is a mixture of an appropriate amount of N-PEO and polyurethane. It can be seen from the data in Table 1 that the cycle performance of the lithium metal battery prepared by using polyoxyethylene (N-PEO, degree of polymerization 6000) modified with terminal amino groups as the uncrosslinked polymer and the mass ratio of the polyoxyethylene (N-PEO, degree of polymerization 6000) to the elastic network is 1:1, and in the prepared lithium metal battery gel electrolyte, the sum of the mass content of polyoxyethylene (N-PEO, degree of polymerization 6000) modified with terminal amino groups and the three-dimensional organic crosslinked network is 4%, and the molar ratio of the monomer to the crosslinking agent in the three-dimensional organic crosslinked network is 100:1.
[0162] Comparative Examples 1 and 2 are both conventional single-network cross-linking systems, which have a negative coupling relationship between mechanics and adhesion. From the data in Table 1, it can be seen that increasing the cross-linking density can effectively improve the bulk mechanical properties of the gel electrolyte, but the freedom of movement of the interfacial polymer will be significantly reduced, resulting in worse cycle performance. It can be seen that the single-network cross-linking system cannot simultaneously improve the bulk mechanical properties and interfacial adhesion of the gel electrolyte.
[0163] The gel electrolyte containing a semi-interpenetrating network structure including uncross-linked polymers and a three-dimensional organic cross-linked network in the embodiment of the present application not only has good bonding strength with the electrode, which is beneficial to suppressing the uneven contact between the electrode and the gel electrolyte caused by the volume expansion of the electrode during the charge and discharge process, but also has good mechanical properties, which is beneficial to maintaining structural stability during the cycle process, thereby achieving better battery cycle performance.
[0164] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium metal battery, characterized in that: include: Gel electrolyte; The gel electrolyte comprises an uncrosslinked polymer and a three-dimensional organic crosslinked network, wherein the uncrosslinked polymer and the three-dimensional organic crosslinked network interpenetrate each other to form a semi-interpenetrating network structure; The uncrosslinked polymer satisfies at least one of the following conditions: Condition a: The degree of polymerization DP of the uncrosslinked polymer satisfies: 1000≤DP≤100000; Condition b: The length of the Kuhn segment in the uncrosslinked polymer is less than 5 nm.
2. The lithium metal battery according to claim 1, characterized in that The three-dimensional organic cross-linked network includes monomers containing polymerizable groups; The polymerizable group includes any one of a double bond, an amino group, a carboxyl group or a hydroxyl group; Preferably, the monomer includes at least one of methacrylate, sodium acrylate, acrylamide, vinylene carbonate, adipic acid, and polyethylene glycol.
3. The lithium metal battery according to claim 2, characterized in that The molar weight of the monomer containing the polymerizable group is n', and the molar weight of the cross-linking agent is n", which satisfies: 10:1≤n' / n"≤1000:
1.
4. The lithium metal battery according to claim 1, characterized in that The uncrosslinked polymer comprises at least one of polyoxyethylene, terminal-modified polyoxyethylene, polyurethane, polycarbonate or polyphosphate; Preferably, the terminal-modified polyoxyethylene includes terminal-amino-modified polyoxyethylene.
5. The lithium metal battery according to claim 1, characterized in that Based on the mass of the gel electrolyte, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 10 to 0.5:
1.
6. The lithium metal battery according to claim 1, characterized in that Based on the mass of the gel electrolyte, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 1 wt% to 10 wt%.
7. The lithium metal battery according to claim 1, characterized in that The gel electrolyte has a loss angle tanδ>1.
8. The lithium metal battery according to any one of claims 1 to 7, characterized in that: At least one of the following conditions is met: (1) The degree of polymerization DP of the uncrosslinked polymer satisfies: 5000≤DP≤7000; (2) The three-dimensional organic cross-linked network is obtained by polymerization of a monomer and a cross-linking agent, the molar weight of the monomer is n′, the molar weight of the cross-linking agent is n″, and the following conditions are satisfied: 50:1≤n′ / n″≤200:1; (3) Based on the mass of the gel electrolyte, the sum of the mass content of the uncrosslinked polymer and the mass content of the three-dimensional organic crosslinked network is 3% to 5%; (4) Based on the mass of the gel electrolyte, the mass ratio of the uncrosslinked polymer to the three-dimensional organic crosslinked network is 2:1 to 0.8:
1.
9. An electrical device, characterized in that: The electrical device contains the lithium metal battery according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of semi-interpenetrating network polymer gel electrolyte membrane
CN105098233A
Semi-interpenetrating network flame-retardant solid-state lithium ion electrolyte, solid-state lithium battery and preparation method
CN111326789A